Photo-powered stretchable nano-containers based on well-defined vesicles formed by an overcrowded alkene switch. Issue 81 (19th September 2016) - Yu, Jing-Jing; Cao, Zhan-Qi; Zhang, Qi; Yang, Shun; Qu, Da-Hui; Tian, He
Abstract : A novel photo-responsive nano-container was successfully constructed based on well-defined vesicles formed by an amphiphilic overcrowded alkene switch. Abstract : A novel photo-responsive nano-container was successfully constructed based on well-defined vesicles formed by an amphiphilic overcrowded alkene switch. The nano-container could adjust its inner volume in reversible photo/heat controlled mode, which could show potential in remote drug delivery systems.